The Influence of Maternal Age on Stunting Toddlers in Balung Lor Village, Balung District - Efa Ernawati; I Gusti Ayu Karnasih; Syska Atik M; Ilmah Fakhriza (Jurnal Kesehatan dr. Soebandi, 2024)
Stunted toddlers represent a chronic nutritional problem that is influenced by maternal conditions. The intra-uterine growth and development of the fetus, as well as the postnatal development of toodlers,  are influenced by maternal factors. This study aims to analyze the effect of maternal age during pregnancy on the inscidence of stunting in toddlers. The design of this study is a comparative analytic method with a retrospective approach. The population is all mothers with stunted children aged 0-59 months, totalling 178 toddlers. A sample of 123 was taken using random sampling technique.  Data were collected using observation sheets. The obtained data then were analyzed using chi square test. There was no effect of maternal age during pregnancy  on the incidence of stunting in toddlers (p value = 0.649). Very short stunted in toddlers is observed among those whose mothers were in the category of healthy reproductive age (20-35 years). Maternal age during pregnancy is not the main factor causing stunting.  So it is necessary to research other causal factors.